A critical review of practices of inclusion and exclusion in the psychology curriculum in higher education - Carolissen, Ronelle (PINS-Psychology in Society, 2024)
Much of South African psychology has pursued the national imperative of critical engagement and reconstruction since 1994, in spite of collusion with Apartheid ideologies before 1994. Critical psychologists who mobilised against apartheid were also active post-1994 in reshaping the discipline and profession. Many of these efforts were directed towards curriculum development to attempt to challenge the dominance of western and northern scholarship in psychology by developing multiple texts that represented local experiences and challenged traditional asocial and ahistorical thinking in psychology. This paper presents critical thoughts on contemporary psychology in higher education, with a particular focus on progress made in curriculum transformation and demographic representativity, to interrogate the extent to which the profession continues to reproduce existing patterns of privilege and inclusion/exclusion. We suggest that considering curriculum as discourse which acts to reproduce larger power relations in society, may be a useful approach to think about inclusion and transformation of the curriculum in psychology.